Description of Terms in Uzbek - Akhmadiev N.M; Andapulatova F.I (Open Academia, 2023)
In this article, with the help of examples, the place of terms in the language, the sources of enrichment, their thematic classification are presented, the etymological layer is classified, the characteristic features of vocabulary are listed, and their explanation is given. highlighted
Keywords: national lexicon; word-terms; professional lexicon